MODELAGEM DA INTENSIDADE DOS VENTOS EM BRASÍLIA-DF POR MEIO DE CADEIAS DE ORDEM VARIÁVEL - MOREIRA, Lucas; UMEDA, Tatiana Keiko Borges (Brazilian Journal of Biometrics, 2020)
In this work, we propose scalable models of variable order for the intensity of the winds in the city of Brasília - DF. This means that, in order to predict the intensity of the wind on a given day, we consider the history of intensities from the previous days. The number of days required to make a forecast depends on the history of the wind intensities in that city. Initially, we considered the perfect measurements of the average wind speed in the city of Brasília corresponding to the period from 21/08/1961 to 7/15/2019. Through this data set, we can indicate the chances of a certain number of strong days or not. Then, the dividends are applied in two parts, one corresponding to the period before 2000 and the other associated to the period after this milestone. Estimates of the variable order models corresponding to these two periods, were shown when there was a change in the wind regime in the city of Brasília in recent years.